On quaternions with incomplete fibonacci and lucas numbers components - Kizilates, Can (Utilitas Mathematica, 2022)
In this paper, we introduce the incomplete Fibonacci and Lucas quaternions. We give recurrence relations, generating functions and some properties of these quaternions. © 2019 Utilitas Mathematica Publishing Inc.. All rights reserved.